Applied public relations cases in stakeholder management - McKee, Kathy Brittain (Routledge communication series., 2009)
Applied Public Relations provides readers with the opportunity to observe and analyze how contemporary businesses and organizations interact with key groups and influences. Through the presentation of cases covering a wide variety of industries, locations. and settings, authors Kathy Brittain McKee and Larry F. Lamb examine how real organizations develop and maintain their relationships, offering valuable insights into contemporary business and organizational management practices.